The Effect of Patient Relationship Management on Patient Loyalty in Buea, Cameroon: Mediating Role of Patient Satisfaction - Divine Mbuwel; Japheth Ahmed; Laurine Nwosu; Jennifer Aigbiremhon (Quantitative Economics and Management Studies, 2023)
Patient Relationship Management (PRM) has emerged as a pivotal strategy within the healthcare sector, aiming to cultivate strong patient-provider relationships and bolster patient satisfaction. This study investigates the influence of PRM on patient loyalty, with a focus on patient satisfaction as a mediating factor. The research delves into established literature and a theoretical framework to elucidate the interconnectedness between the constructs. Through convenience sampling method and data collected from patients who had received medical attention from hospitals operating in Buea, Cameroon, this study offers empirical insights into the critical determinants of patient loyalty in the healthcare industry. Data was drawn from 371 patients in the study area. PRM was found to positively impact patient loyalty. PRM had a significant effect on patient satisfaction and patient satisfaction positively impacted patient loyalty. Furthermore, patient satisfaction was found to partially mediate the relationship between PRM and patient loyalty. Understanding the nuanced relationship between PRM, patient satisfaction, and patient loyalty is vital for healthcare organizations seeking to enhance service quality and foster long-term relationships with their patients through personalised communication, targeted service delivery, and proactive patient engagement.